Long‐term outcomes after prophylactic ICD and CRT‐D implantation in nonischemic patients: Analysis from a nationwide database of daily remote‐monitoring transmissions. (18th June 2019) - Forleo, Giovanni B.; Solimene, Francesco; Pisanò, Ennio C.; Zanotto, Gabriele; Calvi, Valeria; Pignalberi, Carlo; Maglia, Giampiero; Iacopino, Saverio; Quartieri, Fabio; Biffi, Mauro; Caravati, Fabrizio; Curnis, Antonio; et al.
Abstract: Introduction: Clinical trials did not provide conclusive evidence concerning the benefit of prophylactic implantable cardioverter‐defibrillators (ICDs) in patients with severe nonischemic cardiomyopathy (NICM). We aimed to compare incidence of appropriate sustained ventricular arrhythmia (SVA) and device therapy in ischemic cardiomyopathy (ICM) vs NICM ICD and/or cardiac resynchronization therapy (CRT‐D) patients. Methods and Results: We analyzed remote‐monitoring data from devices of the Home Monitoring Expert Alliance network. SVA recordings were adjudicated by three independent electrophysiologists. Our cohort included 1, 946 patients who received either an ICD (55%) or a CRT‐D (45%) for primary prevention of sudden cardiac death. Median (interquartile range) age was 70 (62‐77) years, 81% were male, and 52% were in the ICM group. Patients were remotely monitored for a maximum follow‐up of 5 years. The 5‐year product‐limit estimate of SVA incidence in patients with an ICD was 47.3% (95% confidence interval [CI], 41.0%‐53.9%) in the ICM group and 44.7% (36.9%‐53.3%) in the NICM group. In patients with a CRT‐D, SVA incidence was 45.7% (37.3%‐55.0%) in ICM patients and 49.2% (40.4%‐58.7%) in NICM patients. The adjusted hazard ratio for SVA in the ICM vs NICM group was 0.96 (95% CI: 0.70‐1.30, P = .77) in ICD patients and 0.85 (95% CI: 0.61‐1.18, P = .34) in CRT‐D patients. SVAs triggered appropriate device therapies with similar incidence in all groups. Conclusion: In a large cohort of remotely monitored ICD and CRT‐D recipients, SVA incidence did not significantly differ in ICM and NICM patients.